Impacts of Different Tree Species of Different Sizes on Spatial Distribution of Herbaceous Plants in the Nigerian Guinea Savannah Ecological Zone - Toma Buba (Scientifica)
This study was aimed at finding the impacts of different tree species and individual trees of different sizes on species richness, diversity, and composition of the herbaceous layer. All the three tree species have greatly increased species richness and diversity both within and outside their crown zones compared with the open grassland. Both species richness and diversity were found to be higher under all the three tree species than outside their crowns, which was in turn higher than the open field. Daniella oliveri has the highest species richness and diversity both within and outside its crown zone followed by Vitellaria paradoxa and then Parkia biglobosa. The result also revealed that the same tree species with different sizes leads to different herbaceous species richness, diversity, and composition under and around the trees’ crowns. P. biglobosa and V. paradoxa trees with smaller sizes showed higher species richness and diversity under their crowns than the bigger ones. The dissimilarity of species composition differs between the inside and outside crown zones of the individuals of the same tree species and among the different trees species and the open field.